Management merchandising to increase profitability at the point of sale - Viteri Avalos, Kimberly Sofía; López Chicaiza, Melissa Raquel; Almeida Sanchez, Brayan Steeven (mktDESCUBRE; Vol 1 No Especial (2021): Special Edition 4th International Scientific Congress of Administrative and Financial Sciences FADE 2020, 2021)
The purpose of this research was the analysis of management merchandising, to increase the profitability at the point of sale, studying what happens in the establishment and observing that the hangers have an appropriate display of the product and an optimal use of space, in this way it is possible to capture the attention of consumers, in order to generate a greater impact and motivate the purchase action. For the development of this scientific article, the analytical and systemic method was used, in addition it is of bibliographical type, since initially merchandising was considered and an analysis of the 3 types of merchandising was made such as the visual, seduction and management, within this last one diverse strategies or attractive techniques were considered, to increase the profitability through an appropriate communication, so that the market study, the assortment, the linear management, the space, and the profitability are part of the necessary techniques for the analysis of this type of merchandising. Finally, an analysis of two companies that have been successful in merchandising was carried out, concluding that by implementing management merchandising strategies, sales can be maximized.